Recurrent implantation failure: A comprehensive summary from etiology to treatment - Ma, Junying; Gao, Wenyan; Li, Da (Frontiers in Endocrinology, 2023)
Implantation is the first step in human reproduction. Successful implantation depends on the crosstalk between embryo and endometrium. Recurrent implantation failure (RIF) is a clinical phenomenon characterized by a lack of implantation after the transfer of several embryos and disturbs approximately 10% couples undergoing in vitro fertilization and embryo transfer. Despite increasing literature on RIF, there is still no widely accepted definition or standard protocol for the diagnosis and treatment of RIF. Progress in predicting and preventing RIF has been hampered by a lack of widely accepted definitions. Most couples with RIF can become pregnant after clinical intervention. The prognosis for couples with RIF is related to maternal age. RIF can be caused by immunology, thrombophilias, endometrial receptivity, microbiome, anatomical abnormalities, male factors, and embryo aneuploidy. It is important to determine the most possible etiologies, and individualized treatment aimed at the primary cause seems to be an effective method for increasing the implantation rate. Couples with RIF require psychological support and appropriate clinical intervention. Further studies are required to evaluate diagnostic method and he effectiveness of each therapy, and guide clinical treatment.